The estate of the art on digital transformation strategies for businesses - Cisneros, Yolanda Lazo (2024)
This article presents the results of a systematic review of the literature that aims to identify digital transformation strategies in companies. A research is carried out with a consolidated meta-analytic approach, based on the analysis of 221 research articles. Where it is highlighted that the largest number of articles published come from authors of Chinese nationality (43.4% of the top ten countries with the highest number of publications), likewise, that 40.3% of the studies were carried out using the quantitative approach. The study also finds that the main digital transformation strategies in companies are based on; a) leadership and planning, b) knowledge management and c) technological innovation (Industry 4.0). It is concluded that digital transformation in companies requires leadership that achieves the implementation of well-defined strategies, effective change management and a collaborative culture that considers the benefits and effectiveness of knowledge management, in addition to the use of advanced technologies like industry 4.0. In addition, the importance of acquiring digital skills to function effectively in the digital environment is highlighted for taking advantage of technological opportunities.